2017
DOI: 10.1002/adma.201703053
|View full text |Cite
|
Sign up to set email alerts
|

Superwettability of Gas Bubbles and Its Application: From Bioinspiration to Advanced Materials

Abstract: Gas bubbles in aqueous media are common and inevitable in, for example, agriculture and industrial processes. The behaviors of gas bubbles on solid interfaces, including generation, growth, coalescence, release, transport, and collection, are crucial to gas‐bubble‐related applications, which are always determined by gas‐bubble wettability on solid interfaces. Here, the recent progress regarding the study of interfaces with gas‐bubble superwettability in aqueous media, i.e., superaerophilicity and superaerophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
117
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(136 citation statements)
references
References 81 publications
1
117
0
Order By: Relevance
“…The shape of the spherical bubble does not change as time goes on (Figure d). In such water/gas/solid three‐phase system, the bubble's behavior can be regarded as an underwater version of Cassie–Baxter state . The underwater superaerophobicity of the rough mesh has a similar formation mechanism with the underwater superoleophobicity of in‐air superhydrophilic materials .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape of the spherical bubble does not change as time goes on (Figure d). In such water/gas/solid three‐phase system, the bubble's behavior can be regarded as an underwater version of Cassie–Baxter state . The underwater superaerophobicity of the rough mesh has a similar formation mechanism with the underwater superoleophobicity of in‐air superhydrophilic materials .…”
Section: Resultsmentioning
confidence: 99%
“…Gas can appear in water in the form of bubbles. Separating liquid and small gas bubbles has great applicable value, which can avoid the harm caused by those bubbles or cleverly collect useful gas bubbles in a liquid medium . If a solid surface has great bubble‐repellent ability, it will be able to solve some bubbles‐induced problems.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Research studies on either "superhydrophilic" or "superhyrophobic" electrodes have been reported. [16] Research studies on either "superhydrophilic" or "superhyrophobic" electrodes have been reported.…”
Section: Wettabilitymentioning
confidence: 99%
“…1,2 Recently, the fabrication and application of underwater superaerophobic surfaces and superaerophilic surfaces have attracted increasing interests. [1][2][3][4][5][6] An underwater superaerophobic surface generally displays a contact angle (CA) greater than 150 • to a small bubble in water, while the bubble shows the CA value smaller than 10 • on an underwater superaerophilic surface. Yong et al found that fish scales show superaerophobicity while lotus leaves show superaerophilicity in water.…”
Section: Introductionmentioning
confidence: 99%
“…15 Although some underwater superaerophobic and superaerophilic surfaces have been successfully fabricated, the related research is still at an initial stage. 1,2,[16][17][18] Those artificial materials usually have single and fixed super-wettability to underwater bubbles, either underwater superaerophobicity or underwater superaerophilicity. To obtain multifunctional applications, a smart surface that can reversibly switch between underwater superaerophobicity and superaerophilicity by a simple way is especially significant but has not been reported until now.…”
Section: Introductionmentioning
confidence: 99%